1982
DOI: 10.1111/j.1432-1033.1982.tb06800.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Rate of ATP Synthesis and H+ Electrochemical Gradient in Rat‐Liver Mitochondria

Abstract: The relationship between rate of ATP synthesis, JATp, and value of the proton electrochemical gradient, A f i~ has been analyzed in intact mitochondria.Onset of phosphorylation causes a depression of AfiH of 1.5 kJ/mol. There is a close parallelism between inhibition of &rp and restoration of A i H to its state-4 value during titrations with oligomycin or atractyloside.Titrations The consistence of the present data with either a chemiosmotic model where AFH is the sole and obligatory intermediate for energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 56 publications
5
50
0
Order By: Relevance
“…These results were recently confirmed in [3]. Authors in [4] observed this effect with submitochondrial particles.…”
Section: Introductionsupporting
confidence: 65%
“…These results were recently confirmed in [3]. Authors in [4] observed this effect with submitochondrial particles.…”
Section: Introductionsupporting
confidence: 65%
“…The former apparently exhibit only one JAT~ vs APH relationship [9] while the latter show several [1,2]; this paper). An analogous difference might exist between chloroplasts [5] and bacterial chromatophores [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Zoratti et al [93] also considered protein-protein interaction as one possible explanation of their experimental results. The direct-collision hypothesis differs from those involving localized protons or localized AfiH +, which require a 'pool' of protons, albeit maybe a small one [32,941, functioning between the two enzymes.…”
Section: Energized Protein Conformationmentioning
confidence: 99%
“…[93]). In consequence, the concentration of uncoupler needed is related only to the concentration of the interacting enzymes concerned in the energy transduction.…”
Section: Energized Protein Conformationmentioning
confidence: 99%